2017
DOI: 10.1021/jacs.7b06659
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Huntingtin Exon 1 Has Similar Overall Structural Features for Wild-Type and Pathological Polyglutamine Lengths

Abstract: Huntington’s disease is caused by expansion of a polyglutamine (polyQ) domain within exon 1 of the huntingtin gene (Httex1). The prevailing hypothesis is that the monomeric Httex1 protein undergoes sharp conformational changes as the polyQ length exceeds a threshold of 36–37 residues. Here, we test this hypothesis by combining novel semi-synthesis strategies with state-of-the-art single-molecule Förster resonance energy transfer measurements on biologically relevant, monomeric Httex1 proteins of five different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
115
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 85 publications
12
115
2
Order By: Relevance
“…In the polyQ:Pfn interaction model, the auxiliary interaction is between the polyQ bead of a Q 40 -C38 molecule and a nonspecific region on the profilin molecule that is distinct from the polyP binding site (Figure 6b). This model accounts for experimental results, which suggest that long polyQ tracts and polyQ aggregates can interact non-specifically with other molecules given the uniformly "sticky" surface of the polyQ domain (73)(74)(75)(76). This model allows for the possibility of a heterotypic multivalent complex in which a single profilin molecule is engaged in two different types of interactions with a Q 40 -C38 oligomer.…”
Section: Modeling Suggests That Profilin Modulates Htt-ntf Phase Behamentioning
confidence: 72%
“…In the polyQ:Pfn interaction model, the auxiliary interaction is between the polyQ bead of a Q 40 -C38 molecule and a nonspecific region on the profilin molecule that is distinct from the polyP binding site (Figure 6b). This model accounts for experimental results, which suggest that long polyQ tracts and polyQ aggregates can interact non-specifically with other molecules given the uniformly "sticky" surface of the polyQ domain (73)(74)(75)(76). This model allows for the possibility of a heterotypic multivalent complex in which a single profilin molecule is engaged in two different types of interactions with a Q 40 -C38 oligomer.…”
Section: Modeling Suggests That Profilin Modulates Htt-ntf Phase Behamentioning
confidence: 72%
“…So far, structural studies on htt exon1 constructs in solution have used computational10 or low‐resolution approaches,10, 11, 12, 13 and focused mainly on the overall properties of the poly‐Q tract. Unfortunately, these studies have reported contradictory observations regarding the conformational preferences of the HR.…”
mentioning
confidence: 99%
“…[9] Ah allmark of HD is the presence of neuronal inclusions containing htt exon1 aggregates that have been linked to the aggregation behavior of poly-Q constructs in vitro. [7,9] So far, structural studies on htt exon1 constructs in solution have used computational [10] or low-resolution approaches, [10][11][12][13] and focused mainly on the overall properties of the poly-Q tract. Unfortunately,t hese studies have reported contradictory observations regarding the conformational preferences of the HR.…”
mentioning
confidence: 99%
“…However, they rely on extensive post-processing such as aggregation purification and solubilization 9,10 . In vitro spectroscopic studies including IR 14 , UVresonance Raman 15,16 , NMR spectroscopy 17 and fluorescence 18,19 on model peptides provide crucial information. But they are typically limited to short expansion length (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…But they are typically limited to short expansion length (e.g. K2Q24K2W) due to the difficulty to isolate the peptides with longer Q [14][15][16][17][18][19] . More importantly, all these in vitro studies cannot recapitulate the native aggregation status in live and complex intracellular environment and lack fine spatial information.…”
Section: Introductionmentioning
confidence: 99%